PERLINDUNGAN HUKUM TERHADAP KORBAN PELECEHAN SEKSUAL DI KOSAN UMUM (STUDI PADA WILAYAH RUNGKUT) - Manista Harwika, Dara; Puspita Sari, Amelia (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
The purpose of this research is to offer novelty related to legal protection that is relevant and can quickly be applied in public boarding houses. Using empirical research methods to describe the legal regulations that live in society. Through this research, the researcher offers the concept of legal protection for victims of sexual harassment who live in an environment that is only limited by one door. Namely that the influence of an environment that is too friendly to teach the individual a touch that should not be done, besides the geographical factor of the environment which is an industrial area with most male workers who only live alone there so they cannot control their passions, besides that the divider between freedoms people per person only one door is considered too thin in protecting each other's privacy so that it is widely used for sexual harassment. In this case, the community around the public boarding house receives two legal protection measures, namely the first, which is preventive, namely building a protection institution for victims of sexual harassment in collaboration with local village officials. The second is to urge the Legislative to immediately pass the Draft law on the Elimination of Sexual Violence because Indonesia is an emergency of sexual harassment. Keywords: legal protection; public boarding houses; sexual harassment Abstrak Tujuan penelitian ini yaitu menawarkan kebaruan terkait perlindungan hukum yang relevan dan cepat dapat diterapkan di dalam kosan umum. Mengunakan metode penelitian empiris dengan menguraikan peraturan hukum yang hidup di masyarakat. Melalui penelitian ini peneliti menawarkan bagaimana konsep perlindungan hukum korban pelecehan seksual yang tinggal di dalam lingkungan yang hanya berbatas oleh satu pintu. Yaitu bahwa pengaruh dari lingkungan yang terlalu ramah sehingga mewajarkan sentuhan yang tidak seharusnya dilakukan kepada individu, selain itu faktor geografis lingkungan yang merupakan kawasan industrial dengan kebanyakan pekerja laki-laki yang hanya tinggal sendirian disana sehingga tidak dapat mengontrol nafsu nya, selain itu sekat diantara kebebasan orang per orang hanya berbatas satu pintu dinilai terlalu tipis dalam melindungi privasi masing-masing sehingga banyak dimanfaatkan untuk melakukan pelecehan seksual. Di dalam hal ini maka masyarakat sekitar kosan umum mendapat dua upaya perlindungan hukum yaitu yang pertama, bersifat mencegah yaitu membangun lembaga perlindungan korban pelecehan seksual yang bekerja sama aparat kampung setempat. Yang kedua yaitu mendesak DPR untuk segera mengesahkan RUU PKS karena Indonesia darurat pelecehan seksual.